Role of the small intestine, colon and microbiota in determining the metabolic fate of polyphenols - Williamson, Gary; Clifford, Michael N. (Biochemical pharmacology, 2017)
[Display omitted] (Poly)phenols are a large group of compounds, found in food, beverages, dietary supplements and herbal medicines. Owing to interest in their biological activities, absorption and metabolism of the most abundant compounds in humans are well understood. Both the chemical structure of the phenolic moiety and any attached chemical groups define whether the polyphenol is absorbed in the small intestine, or reaches the colon and is subject to extensive catabolism by colonic microbiota. Untransformed substrates may be absorbed, appearing in plasma primarily as methylated, sulfated and glucuronidated derivatives, with in some cases the unchanged substrate. Many of the catabolites are well absorbed from the colon and appear in the plasma either similarly conjugated, or as glycine conjugates, or in some cases unchanged. Although many (poly)phenol catabolites have been identified in human plasma and/or urine, the exact pathways from substrate to final microbial catabolite, and the species of bacteria and enzymes involved, are still scarcely reported. While it is clear that the composition of the human gut microbiota can be modulated in vivo by supplementation with some (poly)phenol-rich commodities, such modulation is definitely not an inevitable consequence of supplementation; it depends on the treatment, length of time and on the individual metabotype, and it is not clear whether the modulation is sustained when supplementation ceases. Some catabolites have been recorded in plasma of volunteers at concentrations similar to those shown to be effective in in vitro studies suggesting that some benefit may be achieved in vivo by diets yielding such catabolites.